2015
DOI: 10.2147/ijn.s87011
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin-modified PEGylated liposomes loaded with doxorubicin for targeting delivery to hepatocellular carcinoma

Abstract: Lactoferrin (Lf) is a potential-targeting ligand for hepatocellular carcinoma (HCC) cells because of its specific binding with asialoglycoprotein receptor (ASGPR). In this present work, a doxorubicin (DOX)-loaded, Lf-modified, polyethylene glycol (PEG)ylated liposome (Lf-PLS) system was developed, and its targeting effect and antitumor efficacy to HCC was also explored. The DOX-loaded Lf-PLS system had spherical or oval vesicles, with mean particle size approximately 100 nm, and had an encapsulation efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…The use of Lf-loaded liposomes as anti-cancer drug carrier has also been tested [201,202]. In particular, bLf-containing polyethylene glycol (PEG)-modified liposomes have been employed in the targeting of Dox in in vitro and in vivo models of hepatocarcinoma, showing a relevant effect in improving Dox cellular uptake, which was associated to the presence of asialoglycoprotein receptors on cancer cell membrane, and to a significant inhibition of tumor growth in mice bearing HepG2 xenografts compared to mice injected intravenously with the sole Dox-loaded PEGylated liposomes [201].…”
Section: Lactoferrin As a Cargo For Cancer Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Lf-loaded liposomes as anti-cancer drug carrier has also been tested [201,202]. In particular, bLf-containing polyethylene glycol (PEG)-modified liposomes have been employed in the targeting of Dox in in vitro and in vivo models of hepatocarcinoma, showing a relevant effect in improving Dox cellular uptake, which was associated to the presence of asialoglycoprotein receptors on cancer cell membrane, and to a significant inhibition of tumor growth in mice bearing HepG2 xenografts compared to mice injected intravenously with the sole Dox-loaded PEGylated liposomes [201].…”
Section: Lactoferrin As a Cargo For Cancer Targetingmentioning
confidence: 99%
“…The use of Lf-loaded liposomes as anti-cancer drug carrier has also been tested [201,202]. In particular, bLf-containing polyethylene glycol (PEG)-modified liposomes have been employed in the targeting of Dox in in vitro and in vivo models of hepatocarcinoma, showing a relevant effect in improving Dox cellular uptake, which was associated to the presence of asialoglycoprotein receptors on cancer cell membrane, and to a significant inhibition of tumor growth in mice bearing HepG2 xenografts compared to mice injected intravenously with the sole Dox-loaded PEGylated liposomes [201]. Moreover, the intravenous injection of Dox-loaded holo-bLf-liposomes in a murine model of breast cancer resulted, along with a high accumulation of the nanocomposites in the tumor site, in tumor suppression and in a higher induction, when compared to mice treated with the sole Dox-loaded liposomes, of hydrogen peroxide conversion to oxygen, due to the release of ferric ions following holo-bLf degradation [202].…”
Section: Lactoferrin As a Cargo For Cancer Targetingmentioning
confidence: 99%
“…Their results demonstrated that the targeting and dual delivery of both drugs gave rise to enhanced therapeutic effects compared to non-targeted or single drug liposomes. Wei et al investigated liposomes made of soybean phosphatidylcholine/cholesterol which was PEGylated to deliver DOX [79]. PEGylation is advantageous as it increases circulation time and avoids rapid clearance by the reticuloendothelial system [80,81].…”
Section: Lipid-based Particlesmentioning
confidence: 99%
“…DOX, also known by one of its trade name Adriamycin, is one of the most common drugs used in liver cancer therapy and in many biomaterial based therapies [58,65,77,79,82,83,93,96,108,109,111]. Besides DOX, taxel-based drugs, such as docetaxel and PTX, are often used in biomaterial based therapies for HCC as well [57,59,87,98].…”
Section: Chemotherapymentioning
confidence: 99%
“…Moreover, PEGylated doxorubicin in thermosensitive liposomes were formulated in order to differentiate the drug release decreasing tumour growth [ 215 ]. Lactoferrin considered as a target-ligand for hepatocellular carcinoma cells was applied as a modifying agent to PEGylated liposomes encapsulating doxorubicin, showing significantly strong antitumor efficacy [ 216 ].…”
Section: Types Of Nanocarriersmentioning
confidence: 99%